Improving Teacher Competence through Training in the Qur’anic Reading and Writing Method at Tadika Al Fikh Orchard, Malaysia - Ibrahim Hasan; Eka Cahyani (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve teachers’ competence in Qur’anic reading and writing instruction through training on Qur’anic literacy methods at Tadika Al Fikh Orchard, Malaysia. The problems faced by the partner institution included the lack of variation in Qur’anic teaching methods and teachers’ limited ability to apply effective and engaging learning techniques for early childhood students. The implementation method consisted of observation, material presentation, demonstrations, direct practice, and evaluation stages. This training provided teachers with an understanding of systematic, interactive, and practical methods for teaching Qur’anic reading and writing. The results of the activity indicated an improvement in teachers’ understanding and skills in teaching Qur’anic literacy to students. In addition, teachers became more confident in applying creative and enjoyable learning methods. Through this activity, it is expected that the quality of Qur’anic learning at Tadika Al Fikh Orchard Malaysia will continue to improve sustainably.